Systemic Analysis on the Features of Immune Microenvironment Related to Prognostic Signature in Head and Neck Squamous Cell Carcinoma - Su, Kaixin; Zhou, Zekun; Yi, Qiao; Liu, Junjie; Luo, Tiao; Cui, Xinyan; Zhang, Haixia (Frontiers in Genetics, 2022)
Background: Head and neck squamous cell carcinoma’s tumor immune microenvironment (TIME) plays important roles in tumor genesis and progression, but its clinical significance remains unclear. Therefore, TIME needs to be better understood in order to improve the response of diagnosis and therapy. Methods: The gene expression and clinical data of 569 HNSCC patients were obtained from The Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO). Immune-related genes(IRGs) from ImmPort database were used for immunotyping of HNSCC patients, and independent GEO were used for subtype verification and comprehensive molecular identification. Results: The patients was divided into three subtypes(C1, C2, and C3) related to different gene expression profiles. Three subtypes showed widely different patterns in tumor genetic distortion, immune cell composition, cytokine profile and so on, verifying that immune-enhanced C2 subtype was associated with better prognosis, in addition, the stroma-deficient C1 subtype may be more efficient for the immune response than the C3 subtype. Futhermore, by WGCNA on the IRGs of those three subtypes, we found two C2-positived gene modules closely related to infection- and immune-associated pathways in the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway database, and the two modules had 22 common pathways. Conclusions: This study improve the power for prognosis prediction and develop new therapeutic strategies to stratify HNSCC patients into clinically significant groups through TIME-related prognostic signature.